Effect of Fermentation Duration and Dosage of EM4 on Maturity Level and Quality of Fermented Compost Fertilizer. - A. Sadeli; Hasnudi; Indrayani Br Sinuraya, Liberty (Talenta Publisher, 2022)
Livestock waste often causes pollution around the cage. Processing of livestock waste such as compost can be used as fertilizer for plants with good enough nutrient content given to plants.Â In order to produce good compost, it require a fermentation process. One way that is rarely used to determine the maturity level of compost is by measuring the carbon dioxide gas content in fermented compost. Measurement of carbon dioxide gas can be done using a tool in the form of a carbon dioxide sensor. The research design used was a 7 x 3 randomized block design with 2 replications, while the parameters studied were N, P, K, Moisture Content, pH, Temperature, C/N, Carbon Dioxide.